Determination of alkali treatment conditions effects which influence the variability of kenaf fiber mean cross sectional area - Hashim, Mohd Yussni; Roslan, Mohd Nazrul; Mohd Zin, Shahruddin Mahzan; Ariffin, Saparudin (2013)
Fiber cross sectional area value is a crucial factor in determining the strength properties of natural fiber. Furthermore, unlike synthetic fiber, a diameter and cross sectional area of natural fiber has a large variation along and between the fibers. This study aims to determine the main and interaction effects of alkali treatment conditions which influence kenaf bast fiber mean cross sectional area. Three alkali treatment conditions at two different levels were selected. The conditions setting were alkali concentrations at 2 and 10 w/v %; fiber immersed temperature at room temperature and 1000 C; and fiber immersed duration for 30 and 480 minutes. Untreated kenaf fiber was used as a control unit. Kenaf bast fiber bundle mounting tab was prepared according to ASTM C1557-03. Cross sectional area was measured using a Leica video analyzer. The study result showed that kenaf fiber bundle mean cross sectional area was reduced 6.77% to 29.88% after alkali treatment. From analysis of variance, it shows that interaction of alkali concentration and immersed time has a higher magnitude at 0.1619 compared to alkali concentration and immersed temperature interaction which was 0.0896. For the main effect, alkali concentration factor contributes to the higher magnitude at 0.1372 which indicated are decrease pattern of variability when the level was change from lower to higher level. Then, it was followed by immersed temperature at 0.1261 and immersed time at 0.0696 magnitudes.